Analytical method development for determining polycyclic aromatic hydrocarbons and organophosphate esters in indoor dust based on solid phase extraction and gas chromatography/mass spectrometry. Issue 7 (3rd February 2016) - Ruan, Xinchao; Lu, Qian; Yang, Zeyu
Abstract : A sample preparation method was optimized for the determination of polycyclic aromatic hydrocarbons (PAHs) and representative organophosphate esters (OPEs) in indoor dust. Abstract : A sample preparation method was optimized for the determination of polycyclic aromatic hydrocarbons (PAHs) and representative organophosphate esters (OPEs) in indoor dust. The method is based on the combination of solid phase extraction (SPE) with gas chromatography-mass spectrometry. The results indicate that 15 mL of a mixture of dichloromethane (DCM) and hexane with a volume ratio of 1 : 1 could elute 25 PAHs from a 3 g silica gel column effectively, followed by 20 mL of acetone used to elute 8 OPEs without any co-elution with PAHs. Matrix effects were investigated by spiking sodium sulfate and dust with analyte standards. For PAHs and OPEs, the recoveries were determined to range from 73.7% to 96.4%, and 56.6 to 96.0%, respectively; precision for 7 replicate analyses ranges from 9.1 to 37.9 and 4.1 to 20.9% relative standard deviation (RSD); method detection limits for quantification were determined to range from 1.57 to 6.58 ng g −1 and 1.40–768 ng g −1, respectively. The application of the developed method for the analysis of 14 real indoor dust samples indicates that PAHs are dominant in all samples. The diagnostic analysis suggests that PAHs are dominantly sourced from the incomplete combustion of fossil fuel and biomass. The detection frequency of OPEs varies with individual congeners. Generally, chlorinated and high molecular OPEs were detected in all dust samples, followed by light molecular ones, but tri(2-butoxyethyl) phosphate was only detected in part of the samples. Similarly, the levels of the OPE congeners with low molecular weights are relatively low compared with chlorinated and higher molecular weight congeners.